Health and AIDS in 2019 and Beyond - Whiteside, Alan (Taylor and Francis, 2019)
Editorials provide an opportunity for the authors to get ideas out and things off their chests. Between us we have a sobering 70 years of experience working on health, initially in Southern Africa. We watched with horror as the HIV epidemic progressed inexorably in the 1980s through Zimbabwe (where David was based) to South Africa in the 1990s (where Alan worked at the University of Natal). HIV was a new disease but swept through the region with unbelievable speed and ferocity. A survey in Northern KwaZulu-Natal in 1986/87 found no HIV, by 2018 prevalence among pregnant women was over 50 percent.